532 OUTCOME OF QUILICI'S HEPATIC SHOULDER PROCEDURE TO AUGMENT LAPAROSCOPIC HIATOPLASTY IN LARGE OR RECURRENT HIATAL HERNIA. (17th September 2021) - Zacherl, Johannes; Kertesz, Viktoria; Höfle, Cordula; Gensthaler, Lisa; Eltschka, Bernhard; Albinni, Said; Schneider, Florian; Schima, Wolfgang; Sitzwohl, Christian; Radlspöck, Wolfgang
Abstract:  : Laparoscopic hiatoplasty and fundoplication is the gold standard of surgical treatment of GERD and hiatal hernia. However, the main drawback of laparoscopic hiatal hernia repair is a substantial recurrence rate. Hence, prosthetic meshs have been used to reduce the risk for recurrence. But meshs may cause major complications. As a consequence we adopted the hepatic shoulder plasty described by Quilici to augment the hiatal hernia repair in patients with a high risk for hernia recurrence. Methods: Patients with large (>4 cm) axial hiatal hernia, giant paraesophageal or with recurrent hernia consecutively underwent laparoscopic hernia repair with crural sutures and hepatic shoulder plasty. A Toupet or a floppy Nissen fundoplication was added. In patients with giant paraesophageal hernia the hernia sack was resected. Perioperative complications were recorded. Follow-up comprised endoscopy and/or radiography and QoL-evaluation with the Eypasch score (GIQLI). Results: Between 2012 and 2018 51 patients (mean age 71 years, 65% female) underwent Quilici's procedure. Among them 33, 3% had one or more previous hiatal hernia repair. There were no conversions. Postoperative complication rate was 7.8%. At follow-up after 2 years 6 recurrences (12%) were encountered, 4 of them were symptomatic (8%). One patient underwent reoperation due to hernia recurrence. In 84% QoL was significantly improved at follow-up. Conclusion: In patients with high risk of recurrence, biological augmentation of the hiatal closure with the left lobe of the liver may be a valuable alternative to prosthetic reinforcement. We observed no complication attributable to liver lobe transposition.